Analisis Nilai Tambah Dan Kelayakan Usaha Keripik Ubi Kayu (Manihot Utilissima) Cap Sinar Jago - Oktavia Niken Marta Primentari (BiSTeK Pertanian, 2021)
Cassava is one of the local food that is widely used by the community as a food substitute for rice, wheat and corn. One of the processed foods made from raw cassava is Cassava Chips. The purpose of cassava processing activities to be chips is to increase the sale value, increase public interest to consume cassava processed products and earn high income. The purpose of this research is to know the value added of cassava processing business into cassava chips and to know the feasibility of cassava chips business. This research was conducted on the business of cassava chips "Cap Sinar Jago" in Talok Village, Turen Subdistrict, Malang Regency. Respondents in this study are business owners and employees of production and marketing. The analysis used to analyze value added by using Hayami method and business feasibility using B/C Ratio, NPV and IRR analysis.